A percepção docente acerca do componente curricular projeto de empreendedorismo ministrado no ensino médio público do estado de Pernambuco - Silva, Noêmia Karina Araújo da (2017)
The present research had the objective of studying the teacher perception about the project of Entrepreneurship as a Curriculum Component taught in the public High Schools of the State of Pernambuco, Brazil. For that, a qualitative research was carried out, with fifteen teachers from the Gerência Regional de Educação Recife Sul (Regional Management of Education - South Recife), using interviews to obtain the professional life experiences of each teacher. At the beginning of this research it was necessary to seek for theoretical references that subsidized basic concepts inherent to the central themes. In this sense, for the accomplishment of this study it was necessary to know the historical origin of the Entrepreneurship and its link with the formal education; also understanding its incorporation in the processes associated to the projects of the entrepreneurial education in the Pernambuco state, supported by the authors that board this innovative tendency in the school environment; beyond to outline a current panorama on High School teaching in Brazil and its restructuring in the State of Pernambuco, with basis on the contributions of Delors' 'Four Pillars of Education' (1998). After the interview, and using norms for the transcription, it was proceeded the analysis of the content of the testimonies given by the interviewed teachers. The results of the statements with similarities concerning to the professional experience showed the confrontations in the educational practice reported by the teachers involved in the project of educational entrepreneurship.